Uji Lapangan Skala Kecil Tentang Pengaruh Kahut Panas Chlorpyrifos Terhadap Nyamuk Aedes aegypti dan Anopheles aconitus - Sugeng Juwono Mardihusodo Sugeng Juwono Mardihusodo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1988)
Sugeng Juwono Mardihusodo, Kasumbogo Dengue Haemorrhagic Fever (DI-IF) and malaria are two major diseases of public health importance in Java, and other areas of Indonesia. Chemical insecticides are still the main weapon in the control of the disease vectors particularly in epidemic situations. In case of malaria vector control, mainly in Java, one of the problems encountered in the field is the development of highly resistant strain of Anopheles aconitus to DDT. Efforts should be taken, therefore, to find a better and more effective insecticide for controlling the vector.Clorpyrifos (Lorsban *180 EC) at doses of 100 ml/ha, 200 ml/ha. and 300 ml/ha applied as thermal fog was proved to be highly effective for controlling Aedes aegypti and An. aconitus mosquitoes, equal to that of malathion at the dose of 438 ml/ha..Considering the effectiveness and efficiency of the control, the recommended dose of chlorpyri - fos for two species of mosquitoes is 100 ml/ha.Key Words: thermal fog — chlorpyrifos — malathion — Aedes aegypti — Anopheles